Prenatal DNA Sequencing: Clinical, Counseling, and Diagnostic Laboratory Considerations. (17th April 2017) - Abou Tayoun, Ahmad N.; Spinner, Nancy B.; Rehm, Heidi L.; Green, Robert C.; Bianchi, Diana W.
Abstract: Clinical diagnostic laboratories are producing next‐generation sequencing‐based test results that are becoming increasingly incorporated into patient care. Whole genome and exome sequencing on fetal material derived from amniocytes, chorionic villi, or products of conception is starting to be offered clinically in specialized centers, but it has not yet become routine practice. The technical, interpretation, and ethical challenges are greatest in the area of prenatal medicine because the fetus has a limited health history, and the physical examination is only indirectly available via prenatal sonography. Here, we provide an overview of these challenges and highlight the clinical utility, reporting, and counseling issues associated with prenatal DNA sequencing. Future considerations are also discussed. © 2017 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Clinical exome and genome sequencing on fetal material (amniotic fluid, chorionic villus sampling, and products of conception) is starting to be offered in specialized centers. There are no technical or interpretation standards/guidelines for the clinical practice of prenatal sequencing. What does this study add? This study highlights a comprehensive overview of prenatal clinical exome and genome sequencing workflow. This study pinpoints challenges and potential solutions at each step of the prenatal sequencing workflow including technical, bioinformatics, interpretation, counseling, and clinical challenges.